Death Came as a Sting: A Case Report - Shankar M Bakkannavar (International Journal of Medical Toxicology and Legal Medicine, 2024)
Various species possess stings that can induce pain and are generally avoided by people. The sting of a bee, in particular, can result in not only a painful experience but also pose a potential threat to life for many individuals. It can trigger severe allergic reactions, leading to a life-threatening condition known as anaphylaxis. Instances of fatalities attributed to anaphylaxis following bee stings have been documented in the literature. Occasionally, complications arising from bee stings can contribute to the demise of the victims. Presented here is a case involving a 64-year-old adult male who was brought to the hospital already deceased. Upon examination, multiple bee stings were observed across the body, with the stingers still intact in some areas. Additionally, two deceased honeybees were found on the victim's body. During the autopsy, congested internal organs were identified, and postmortem blood biochemical analysis revealed elevated levels of Immunoglobulin E and serum creatinine.